Finite element studies of bolted, riveted, bonded and hybrid step-lap joints of thick plate. (2022) - Mistry, Smit; Joshi, Poojan; Dhandhukiya, Rahul; Gandhi, Shivam; Bhanushali, Nayan; Desai, Chirag
Abstract: The application of the step lap joint has been increased due to its good characteristics such as lightweight, high stiffness, and good fatigue durability. Moreover, it has a wide application in the aerospace, automotive and marine sector because of its efficient strength and less stress concentration. The present study is concentrated on the effect of the kind of joint used for lap joint like the adhesive joint, riveted joints, and bolted joints. In addition, the length of the steps has been changed to study the behavior of adhesive lap joint in detail. Also, the hybrid joint such as a bolted-adhesive and riveted-adhesive joint is examined in the current study. The variation in the number of bolts and rivets are made for detailed analysis. The main objective of this project is to analyze the step lap joint with different length, different material for adherend and adhesive and also compare it with different mechanical fasteners such as rivets and bolts considering hybridization of it with and without the adhesive, Finite Element Analysis (FEA) is carried out in ANSYS Workbench for analysis and SolidWorks software is used for 3-D modelling.